2011
DOI: 10.1103/physrevb.83.115418
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of theLaFeO3(010) surface determined from first-principles and thermodynamic calculations

Abstract: The phase diagram of LaFeO 3 (010) surfaces is developed by Ab-initio thermodynamics.The stabilities of LaO-and FeO 2 -terminated surfaces are investigated at temperatures representative of solid oxide fuel cell (SOFC) operating conditions (773 K, 1073 K, and 1223For LaO-type surfaces, it is predicted that the most stable surface structure is oxidized at all temperatures considered. For FeO 2 -type surfaces, the most stable surface structure is predicted to change from oxidized (at 773 K) to stoichiometric (at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…These contributions would be needed to resolve, as a function of the temperature, an inversion of stability between two terminations separated by a few tens of meV. [52][53][54] The surface energies found in this work are well separated by a few hundreds of meV and these contributions can be safely neglected in a first approximation. Doing that, the surface grand potential has no more explicit temperature dependence but keeps an implicit one via the oxygen chemical potential.…”
Section: Ab Initio Atomistic Thermodynamicsmentioning
confidence: 85%
“…These contributions would be needed to resolve, as a function of the temperature, an inversion of stability between two terminations separated by a few tens of meV. [52][53][54] The surface energies found in this work are well separated by a few hundreds of meV and these contributions can be safely neglected in a first approximation. Doing that, the surface grand potential has no more explicit temperature dependence but keeps an implicit one via the oxygen chemical potential.…”
Section: Ab Initio Atomistic Thermodynamicsmentioning
confidence: 85%
“…Barium titanate (BaTiO 3 , BTO) and lanthanum ferrite (LaFeO 3 , LFO) were chosen because their surfaces have various observed atomic compositions 20,32,33 . Strontium titanate (SrTiO 3 , STO) was chosen to examine the geometric effect using its compositionally identical but geometrically different structures (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…We note that studies of the electronic structure and stability of LaO-and FeO 2 -terminated LaFeO 3 (001) surfaces have previously been performed, motivated by the excellent catalytic activity of this perovskite for the oxygen reduction reaction in solid oxide fuel cells (SOFC). [8][9][10] In that work, Lee et al showed that both LaO-and FeO 2terminated surfaces are available under SOFC operating conditions, while only the FeO 2 -terminated surface can be stable at temperatures higher than 1500 K. 9, 10 Furthermore, it was also revealed that oxygen reduction more easily occurs on the FeO 2 termination than the LaO termination due to the multivalent character of the Fe atom, while the LaOterminated surface is likely to be passivated as a result of a higher O vacancy formation energy and stronger O adsorption energy. [8][9][10] …”
Section: Introductionmentioning
confidence: 99%